“The teacher did not explain the lesson, just giving us a task”: Self-reflections of pre-service English teachers in an online learning mode - Langgeng Budianto; M. Faruq Ubaidillah; Ehsan Namaziandost (International Journal of Education and Learning, 2024)
In the post-pandemic era, online learning has been the focus of many educational institutions nowadays, including English as a foreign language classes. However, with the current rapid changes in online learning, little attention has been paid to uncovering the self-reflection of pre-service English teachers in learning English online. This brief report seeks to construe how three Indonesian pre-service English teachers negotiate the meaning of their past learning experiences in English as a foreign language classes during the online learning mode. We employed a narrative inquiry in this study in order to capture the participants’ experiences. Data were garnered through WhatsApp-based semi-structured interviews and were analyzed narratively. Findings suggest that the participants negotiated their multifaceted learning experiences and complexities during the online learning process. In addition, from the participants’ narratives, teaching and learning enactment done by the teachers was ill-performed. The pedagogical implications of this study are discussed at the end of this paper.